Circular Economy Approaches In Sustainable Engineering: A Systematic Literature Review Of Waste-To-Resource Technologies, Economic Impacts, And Policy Frameworks - Abdul Jamal; Adamu Abubakar (International Journal of Sustainable Engineering Innovations, 2026)
Background of Study: The global challenge of waste management and resource depletion is driven by the traditional linear "take-make-dispose" model. This study addresses the urgent need to transition toward a circular economy (CE) to mitigate environmental degradation and resource scarcity. Aims Paper: To systematically synthesize and analyze existing literature to identify strategic pathways for advancing sustainable engineering through circular economy principles, integrating technological innovation, economic impacts, and policy frameworks. Methods: The research employed a Systematic Literature Review (SLR) following PRISMA 2020 guidelines. Data was sourced from Scopus, Web of Science, and IEEE Xplore (2015–2025). Bibliometric analysis was performed using Biblioshiny and VOSviewer on 15 high-quality selected articles. Result: Findings show that the field is dominated by techno-economic studies (28.6%), Life Cycle Assessment (21.4%), and resource recovery optimization (21.4%). Quantitative modeling and simulations are the primary methodologies used (42.9%). Conclusion: The transition to a circular economy requires an integrated approach linking technical advancement with economic viability and policy support. Future research should bridge the gap between technological innovation and social/digital transformation.